Analyzing the Concept of Speech Act of Thanking in the English Textbooks of Primary Schools (Journal of the College of Basic Education, 2020)
Teaching politeness speech is an important step toward teaching foreign language. Speech act of thanking is the first thing that must be taught at primary schools. The study aims to reveal the degree of existence of the concept of the speech act of thanking in the English for Iraq 6th primary textbook. The researchers used theme, subject, and illustrations as units to analyze the data of the study. The sample of the study was the English for Iraq 6th primary English textbook. The research tries to answer the following questions " To what degree do themes, subject, and illustrations in English for Iraq 6th primary textbook include concept of speech act of thanking? To answer the question, a percentage was used. The results revealed that the concept of speech act of thanking existed with very low percentage in the themes and subject, and there was not existed in illustrations in the 6th primary English textbook.